Composite fiber rubber modified asphalt mixture and preparation method thereof

By adding composite fibers to the rubber-modified asphalt mixture and optimizing the preparation process, the problem of insufficient interface bonding strength and compression deformation resistance after aging of ultra-high-volume rubber-modified asphalt mixture is solved, and significant performance improvement is achieved.

CN119661121APending Publication Date: 2025-03-21中国建设基础设施有限公司 +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311208472.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

After the ultra-high-dose rubber-modified asphalt mixture is aging, the interface bonding strength and compression deformation resistance are insufficient, resulting in unstable interface contact state and weak interlayers in the pavement structure.

Method used

In the process of preparing rubber-modified asphalt mixture, composite fibers (glass fiber and carbon fiber) are added, and by optimizing the material addition sequence and adding ore powder in batches, a stable enhanced interface and multi-angle spatial cross-network structure is formed.

Benefits of technology

The freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus after aging of rubber modified asphalt mixture were significantly improved, with an increase of 7.5% and 70.4% respectively, improving the interface bonding strength and anti-compression deformation ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a composite fiber rubber modified asphalt mixture and a preparation method thereof, belongs to the technical field of asphalt materials, and solves the problems in the prior art that the interface bonding strength and compressive deformation resistance are insufficient after an ultrahigh-content rubber modified asphalt mixture is aged. The preparation method comprises the following steps: step 1, adding preheated stone into a preheated mixing pot, then adding glass fibers, and stirring; step 2, adding the rubber modified asphalt into the mixing pot, and stirring; step 3, adding part of mineral powder into the mixing pot, and stirring; step 4, mixing the carbon fibers and the residual mineral powder; and step 5, adding the mixed carbon fiber and mineral powder into the mixing pot, stirring, and discharging to obtain the composite fiber rubber modified asphalt mixture. According to the invention, the interface bonding strength and compressive deformation resistance of the aged ultrahigh-content rubber modified asphalt mixture are improved at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of asphalt materials, and in particular to a composite fiber rubber modified asphalt mixture and a preparation method thereof. Background Art

[0002] Producing waste tires into waste rubber powder as road asphalt modifiers and making full use of it in highway construction will be one of the best methods of harmless and resource-based treatment recognized internationally. Using rubber asphalt mixture as road paving material can scientifically reduce noise, improve wear resistance, and fully realize the high-value conversion of waste tires. It has significant social and economic value in saving social resources and protecting the environment. How to use waste tires more efficiently and realize the deep recycling of resources has become a difficult problem that needs to be solved urgently.

[0003] At present, the common rubber powder content of rubber modified asphalt in the industry can only be added to about 20%; with the continuous innovation of rubber powder pretreatment technology, the rubber powder content has been increased to more than 30%, that is, the high-content rubber modified asphalt considered by the industry, and the current content of large-scale physical engineering applications is 30% to 40%. In recent years, with the continuous rise in international crude oil prices, the price of base asphalt has also remained high, causing the cost of asphalt pavement to rise sharply. Therefore, reducing the asphalt content in the binder, increasing the rubber powder content, and maintaining sufficient road performance have become the most reasonable technical route at present. As a result, rubber modified asphalt with a content of more than 50% has emerged, that is, ultra-high-content rubber modified asphalt.

[0004] Ultra-high rubber-modified asphalt mixture has further improved its resistance to rutting and low-temperature cracking due to the increase in the rubber powder content. However, during the rubber powder activation process, the physical and chemical treatment methods are used to deeply fracture the original polymer structure of the rubber powder, thereby weakening its original anti-aging and compression advantages. On the one hand, after the asphalt mixture ages, the adhesion of the mortar-sand interface decreases rapidly, resulting in unstable interface contact state and decreased long-term interface bonding strength. On the other hand, it leads to insufficient resistance to compression deformation of the asphalt mixture, and it is easy to form a weak interlayer in the asphalt pavement structure. Today, when the pavement design concept is gradually developing towards "modulus increasing layer by layer", its application scenarios are greatly restricted. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a composite fiber rubber modified asphalt mixture and a preparation method thereof, so as to solve the problem of insufficient interface bonding strength and compression deformation resistance of ultra-high-dosage rubber modified asphalt mixture after aging in the prior art.

[0006] In one aspect, the present invention provides a method for preparing a composite fiber rubber modified asphalt mixture, comprising the following steps:

[0007] Step 1: Add preheated stone to the preheated mixing pot, then add glass fiber and stir;

[0008] Step 2: Add rubber modified asphalt into the mixing pot and stir;

[0009] Step 3: Add some mineral powder to the mixing pot and stir;

[0010] Step 4: Mix the carbon fiber and the remaining mineral powder;

[0011] Step 5: Add the mixed carbon fiber and mineral powder into a mixing pot, stir, and discharge to obtain a composite fiber rubber modified asphalt mixture.

[0012] Optionally, in step 1, the preheating temperature of the mixing pot is 185-195°C.

[0013] Optionally, in step 1, the stirring time is 60s.

[0014] Optionally, the mineral powder in step 3 and step 4 each accounts for 50%.

[0015] Optionally, the mass ratio of the glass fiber to the carbon fiber is 1:3 to 1:5.

[0016] Optionally, the mass ratio of the stone to the mineral material is 96:4.

[0017] Optionally, the grading type of the stone is ARHM-25 type grading.

[0018] Optionally, the rubber-modified asphalt is an ultra-high-content rubber-modified asphalt with a rubber powder mass fraction of more than 70 parts.

[0019] Optionally, in step 5, the stirring time is 90 seconds.

[0020] Optionally, the glass fibers and the carbon fibers have the same length.

[0021] Optionally, the lengths of the glass fiber and the carbon fiber are between the critical sieve hole particle size of stone, the lengths of the glass fiber and the carbon fiber are 7±1 mm, and the critical sieve hole particle size of stone is 4.75-9.5 mm.

[0022] In a second aspect, the present invention further provides a composite fiber rubber modified asphalt mixture, which is prepared by the above-mentioned preparation method.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] (1) The existing ultra-high-content rubber-modified asphalt mixture has a rubber powder content of more than 50%. During the activation of the rubber powder, physical and chemical treatment methods are used to deeply break the original polymer structure of the rubber powder, weakening its original anti-aging and anti-compression advantages, resulting in insufficient interface bonding strength (evaluated by freeze-thaw splitting strength ratio) and anti-compression deformation capacity (evaluated by uniaxial compression dynamic modulus) of the ultra-high-content rubber-modified asphalt mixture after aging. The present invention innovatively proposes to add composite fibers (glass fibers and carbon fibers) during the preparation of the rubber-modified asphalt mixture, so that the freeze-thaw splitting strength ratio of the rubber-modified asphalt mixture after aging is increased from 81.4% to 87.5%, an increase of 6.1%, an increase of 7.5%; the uniaxial compression dynamic modulus is increased from 4070MPa to 6935MPa, an increase of 2865MPa, an increase of 70.4%. The interface bonding strength and anti-compression deformation capacity of the ultra-high-content rubber-modified asphalt mixture after aging are both improved, especially the anti-compression deformation capacity is significantly improved.

[0025] Specifically, with the characteristics of high temperature resistance, good toughness and strong adsorption of glass fiber, it can be effectively wrapped with asphalt to form a stable reinforced interface and improve the interfacial bonding strength. With the characteristics of high stiffness, good spatial dispersion and strong adsorption of carbon fiber, on the one hand, the interfacial bonding strength is further improved, and the overall modulus of the mixture is improved. On the other hand, by forming a multi-angle spatial cross-network structure with glass fiber, the cohesion of the mixture is greatly improved, thereby improving the overall anti-compression deformation ability of the mixture.

[0026] (2) In the process of preparing the rubber-modified asphalt mixture, the present invention optimizes the order of adding materials according to the characteristics of the materials (glass fiber is light and easy to scatter; carbon fiber is dense and easy to sink), that is, the light glass fiber is first dispersed evenly in the stone and then the rubber-modified asphalt is added. This not only reduces the scattering of the glass fiber (because the rubber-modified asphalt is sticky, the glass fiber is wrapped on the rubber-modified asphalt), but also ensures the uniform wrapping of the glass fiber (because the glass fiber has been pre-evenly dispersed in the stone), thereby enabling the glass fiber to form a uniform spatial cross-network structure with the carbon fiber, thereby ensuring the stability and reliability of the overall performance of the rubber-modified asphalt mixture.

[0027] (3) The mineral powder of the present invention is not added all at once, but is added to the mixing pot in batches. Specifically, a portion of the mineral powder is mixed with rubber-modified asphalt wrapped with glass fiber, and the adsorption of the mineral powder is used to make the rubber-modified asphalt more firmly adsorbed on the stone and glass fiber; the other portion of the mineral powder is mixed with carbon fiber, so that the surface of the carbon fiber is first adhered to some mineral powder, which plays an isolation role, so that the carbon fiber can be evenly wrapped on the rubber-modified asphalt, and then the carbon fiber can form a uniform spatial cross network with the glass fiber, ensuring the stability and reliability of the overall performance of the rubber-modified asphalt mixture. If the carbon fiber is added directly to the mixing pot, the carbon fiber will stick to the sticky rubber-modified asphalt, resulting in uneven dispersion of the carbon fiber, affecting the overall performance of the rubber-modified asphalt mixture.

[0028] (4) The present invention controls the lengths of the carbon fibers and the glass fibers to be consistent, which can make it easier to form a cross network during the mixing process and prevent the fibers from being entangled and clumped during the preparation process.

[0029] (5) The present invention controls the length ratio of carbon fiber and glass fiber (consistent length) and controls the length of carbon fiber and glass fiber (7±1mm) between the key sieve hole particle size of stone (4.75-9.5mm), so that after adding the mixed fiber, the increase in the freeze-thaw splitting strength ratio and the uniaxial compression dynamic modulus of the rubber modified asphalt mixture prepared is greater than the increase in the freeze-thaw splitting strength ratio and the uniaxial compression dynamic modulus of the rubber modified asphalt mixture added with glass fiber and carbon fiber respectively, and is greater than the sum of the increase of the glass fiber alone and the carbon fiber alone.

[0030] (6) The present invention provides a mass ratio range with excellent performance and optimal mixing and workability by controlling the mass ratio of glass fiber to carbon fiber to be between 1:3 and 1:5, and the technical solution has strong operability.

[0031] (7) The method for preparing the composite fiber rubber modified asphalt mixture of the present application has a simple process, does not increase the production cost compared with the prior art, and is convenient for large-scale production.

[0032] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can be obvious from the description or understood by practicing the present invention. DETAILED DESCRIPTION

[0033] At present, the common rubber powder content of rubber modified asphalt in the industry can only be added to about 20%; with the continuous innovation of rubber powder pretreatment technology, the rubber powder content has been increased to more than 30%. For example, the invention patents with publication numbers CN112374805A and CN112374806A previously applied by the applicant of the present invention are for large-content rubber modified asphalt (rubber powder content is more than 30%), that is, high-content rubber modified asphalt considered by the industry, and the content of 30% to 40% has been used in large-scale physical engineering applications.

[0034] In recent years, with the continuous rise in international crude oil prices, the price of base asphalt has remained high, causing the cost of asphalt pavement paving to rise sharply. Therefore, reducing the asphalt content in the binder, increasing the rubber powder content, and maintaining sufficient road performance have become the most reasonable technical route at present. As a result, rubber-modified asphalt with a content of more than 50% has emerged, that is, ultra-high-content rubber-modified asphalt.

[0035] The amount of rubber powder added has a great influence on the performance of rubber modified asphalt, which can be confirmed by the data of Group B and Group C of Example 4 of the present invention, and the data of Group B of Example 1 of Patent Publication No. CN112374805A and Group B of Example 1 of Patent Publication No. CN112374806A.

[0036] Specifically, the experiment of Group B of Example 4 of the present invention is similar to the experiment of Group B of Patent Example 1 with Publication No. CN112374806A, with the main difference being that the experiment of Group B of Example 4 of the present invention uses ultra-high-content rubber-modified asphalt, while the experiment of Group B of Patent Example 1 with Publication No. CN112374806A uses high-content rubber-modified asphalt. The average dynamic modulus of the former is 5047 MPa, while the average dynamic modulus of the latter is 7741 MPa, which is very different.

[0037] The experiment of Group C of Example 4 of the present invention is similar to the experiment of Group B of Patent Example 1 with Publication No. CN112374805A, with the main difference being that the experiment of Group C of Example 4 of the present invention uses ultra-high-content rubber-modified asphalt, while the experiment of Group B of Patent Example 1 with Publication No. CN112374805A uses high-content rubber-modified asphalt. The average freeze-thaw splitting strength ratio of the former is 83.1%, while the average freeze-thaw splitting strength ratio of the latter is 89.1%, which is also very different.

[0038] Therefore, the rubber powder content of the rubber modified asphalt mixtures with publication numbers CN112374805A and CN112374806A and the rubber modified asphalt mixture of the present invention is not at the same level, and their performance data are not comparable.

[0039] Ultra-high rubber-modified asphalt mixture has further improved its resistance to rutting and low-temperature cracking due to the increase in the rubber powder content. However, during the rubber powder activation process, the physical and chemical treatment methods are used to deeply fracture the original polymer structure of the rubber powder, thereby weakening its original anti-aging and compression advantages. On the one hand, after the asphalt mixture ages, the adhesion of the mortar-sand interface decreases rapidly, resulting in unstable interface contact state and decreased long-term interface bonding strength. On the other hand, it leads to insufficient resistance to compression deformation of the asphalt mixture, and it is easy to form a weak interlayer in the asphalt pavement structure. Today, when the pavement design concept is gradually developing towards "modulus increasing layer by layer", its application scenarios are greatly restricted.

[0040] The present invention studies ultra-high-content rubber modified asphalt mixture. In order to solve the problem of insufficient interface bonding strength and compression deformation resistance of ultra-high-content rubber modified asphalt mixture after aging in the prior art, in the first aspect, the present invention provides a method for preparing a composite fiber rubber modified asphalt mixture, comprising the following steps:

[0041] Step 1: Add preheated stone to the preheated mixing pot, then add glass fiber and stir for 60 seconds;

[0042] Step 2: Add rubber-modified asphalt into the mixing pot and stir for 60 seconds;

[0043] Step 3: Add some preheated mineral powder into the mixing pot and stir for 60 seconds;

[0044] Step 4: Mix the carbon fiber and the preheated remaining mineral powder;

[0045] Step 5: Add the mixed carbon fiber and mineral powder into the mixing pot, stir for 90 seconds and then discharge the material.

[0046] In the present invention, the mineral material includes stone and mineral powder. The stone acts as a skeleton. The mineral powder can fill the pores of the skeleton on the one hand, and on the other hand, after the mineral powder is mixed with rubber-modified asphalt, the adsorption of the mineral powder is utilized to make the asphalt more firmly adsorbed on the stone and glass fiber.

[0047] In one embodiment, the mass ratio of stone to mineral powder is 96:4. For example, 96 parts of stone and 4 parts of mineral powder.

[0048] The composite fiber referred to in the present invention includes carbon fiber and glass fiber, wherein the carbon fiber is needle-shaped fiber processed from waste carbon fiber products, and the glass fiber is 2400Tex (linear density, g / 1000m) untwisted coarse sand.

[0049] In addition, the carbon fiber and glass fiber used in the present invention are required to have good cutting and antistatic properties from the perspective of processing cost and construction anti-scattering; from the perspective of processing economy, the cutting length should not be too short, and should be close to the length of naturally formed debris, so as to fully utilize waste.

[0050] Considering the functionality of composite fibers, the fiber length should be controlled to be between the key sieve hole particle size of the stone (4.75-9.5mm), specifically 7±1mm. If the fiber length is too long, it is easy to cause entanglement. If the fiber length is too short, it cannot be guaranteed to be dispersed in the core area, thus affecting product performance. By controlling the fiber length to 7±1mm, the filling and interface bonding effects can be guaranteed.

[0051] Considering the synergistic effect of composite fibers, the lengths of the two fibers should be kept consistent. On the one hand, it can make it easier to form a cross network during the mixing process, and on the other hand, it can prevent the fibers from being entangled and clumped during the preparation process.

[0052] It should be noted that the present invention fully takes into account the characteristics of glass fiber being light and easy to scatter, while carbon fiber being dense and easy to sink. If all materials (carbon fiber, glass fiber, stone, mineral powder and rubber-modified asphalt) are mixed and stirred together, it is very easy to cause uneven dispersion of carbon fiber and glass fiber in the mixture, and the two cannot form a uniform spatial cross-network structure, resulting in unstable overall performance of the rubber-modified asphalt mixture.

[0053] Based on the above considerations, the present invention first mixes the glass fiber and stone evenly (step 1), and then adds rubber modified asphalt (step 2), which not only reduces the scattering of the glass fiber (because the rubber modified asphalt is sticky and the glass fiber is wrapped around the rubber modified asphalt), but also ensures the uniform wrapping of the glass fiber (because the glass fiber has been pre-evenly dispersed in the stone), thereby enabling the glass fiber to form a uniform spatial cross-network structure with the carbon fiber, thereby ensuring the stability and reliability of the overall performance of the rubber modified asphalt mixture.

[0054] In a preferred embodiment, the mineral powder is not added all at once, but in batches. Among them, 50% of the mineral powder is mixed with the rubber-modified asphalt wrapped with glass fiber (step 3), and the adsorption of the mineral powder is used to make the rubber-modified asphalt more firmly adsorbed on the stone and glass fiber. The other 50% of the mineral powder is mixed with carbon fiber (step 4), so that some mineral powder is first adhered to the surface of the carbon fiber to play an isolation role, so that the carbon fiber can be evenly wrapped on the rubber-modified asphalt. If the carbon fiber is added directly to the mixing pot, the carbon fiber will stick to the sticky rubber-modified asphalt, resulting in uneven dispersion of the carbon fiber, affecting the overall performance of the rubber-modified asphalt mixture.

[0055] In one embodiment, the present invention first divides the mineral powder weighed according to the grading into two equal parts, and then heats the two parts of mineral powder separately, effectively avoiding temperature loss caused by weighing during the preparation process, and making the mixing more uniform.

[0056] Specifically, in step 1, the preheating temperature of the mixing pot is 185-195°C, and the stone is preheated to 185-195°C. In step 2, the temperature of the added rubber modified asphalt is 185-190°C. This is to ensure the fluidity of the ultra-high-dosage rubber asphalt and prevent the viscosity from increasing due to the decrease in temperature, resulting in agglomeration. In steps 3 and 5, the mineral powder is preheated to 185-195°C respectively.

[0057] In one embodiment, the mass ratio of glass fiber to carbon fiber is 1:3 to 1:5, such as 1:3, 1:4, 1:5. The sum of the mass of glass fiber and carbon fiber accounts for 0.1% to 0.2% of the total mass of the rubber modified asphalt mixture, such as 0.1%, 0.15%, 0.2%.

[0058] In one embodiment, the rubber modified asphalt accounts for 4.5% to 5.0% of the mass of the mineral material, such as 4.5%, 4.6%, 4.7%, 4.8%, 4.9% and 5.0%.

[0059] Specifically, the rubber modified asphalt used in the present invention is an ultra-high-dosage rubber modified asphalt with a rubber powder mass fraction of more than 70 parts. The softening point of the rubber asphalt is not less than 70°C, the rotational viscosity at 180°C is 2.0-4.0 Pa.s, and the elastic recovery at 25°C is not less than 65%, so as to ensure good storage, transportation and working characteristics of the asphalt.

[0060] In one embodiment, the rubber powder used in the rubber modified asphalt has a mesh size of 25 to 30 meshes.

[0061] The price of rubber powder is directly proportional to its fineness. The greater the fineness, the higher the price. Using 25-30 mesh rubber powder can effectively reduce costs while meeting the modification requirements. At the same time, due to the high amount of rubber powder, the mesh range needs to be strictly controlled to ensure the performance stability and consistency of the rubber powder.

[0062] In one embodiment, the stone grading type used in the preparation method of the present invention is ARHM-25 type grading.

[0063] In a second aspect, the present invention further provides a composite fiber rubber modified asphalt mixture, which is prepared by the above-mentioned preparation method. The rubber modified asphalt mixture comprises rubber modified asphalt, composite fiber and mineral material.

[0064] Rubber modified asphalt is an ultra-high-content rubber modified asphalt with a rubber powder mass percentage of more than 70 parts. The softening point of rubber asphalt is not less than 70°C, the rotational viscosity at 180°C is 2.0-4.0 Pa.s, and the elastic recovery at 25°C is not less than 65%, so as to ensure the good storage, transportation and working characteristics of asphalt. The mesh size of the rubber powder used in rubber modified asphalt is 25-30 mesh.

[0065] The composite fiber includes carbon fiber and glass fiber, and the mass ratio of glass fiber to carbon fiber is 1:3 to 1:5, such as 1:3, 1:4, 1:5. The sum of the mass of glass fiber and carbon fiber accounts for 0.1% to 0.2% of the total mass of the rubber modified asphalt mixture, such as 0.1%, 0.15%, 0.2%.

[0066] The carbon fiber is needle-shaped fiber obtained by processing waste carbon fiber products, and the glass fiber is 2400Tex (linear density, g / 1000m) untwisted coarse sand. The length of the carbon fiber and the glass fiber is the same, both 7±1mm.

[0067] The mineral material includes stone and mineral powder, and the mass ratio of stone to mineral powder is 96:4. For example, 96 parts of stone and 4 parts of mineral powder.

[0068] The stone grading type is ARHM-25 grading. Specifically, the ARHM-25 grading stone specifications are 22-30mm, 15-22mm, 11-15mm, 6-11mm, 3-6mm, 0-3mm, and the proportion of each grade of stone is 28 parts, 16 parts, 8 parts, 15 parts, 6 parts, 23 parts, and the mineral powder is 4 parts.

[0069] The rubber modified asphalt accounts for 4.5% to 5.0% of the mineral mass, such as 4.5%, 4.6%, 4.7%, 4.8%, 4.9% and 5.0%.

[0070] The technical application of the present invention is described in detail below in conjunction with embodiments.

[0071] The gradations used in the following examples are all ARHM25 gradations suitable for the lower layer, and the pass rates of each sieve hole are shown in Table 1; the stone specifications used are 22-30mm, 15-22mm, 11-15mm, 6-11mm, 3-6mm, and 0-3mm, and the proportions of each stone are 28 parts, 16 parts, 8 parts, 15 parts, 6 parts, and 23 parts by mass, and the mineral powder is 4 parts. The asphalt used is rubber-modified asphalt with a mass fraction of 70 parts of rubber powder.

[0072] Table 1 ARHM25 grading each sieve hole pass rate (%)

[0073]

[0074] The freeze-thaw splitting strength ratio is used to evaluate the bonding strength of the interface of asphalt mixture after aging and freeze-thaw damage. The specific test steps are as follows: After the mixture is mixed and discharged, it is placed in a 180℃ pressure aging container for 12 hours, and then two groups of Marshall specimens are formed using a Marshall compactor. Each group includes 3 parallel specimens, and the positive and negative sides are compacted 50 times. One group does not undergo freeze-thaw cycles, and the other group undergoes one standard freeze-thaw cycle. After that, the Marshall freeze-thaw splitting test is carried out at the same time. The test temperature is 25℃ and the loading rate is 50mm / min. The splitting tensile strength is calculated based on the maximum test load.

[0075] The uniaxial compression dynamic modulus is used to evaluate the compression deformation resistance of asphalt mixture. The specific test steps are as follows: After the mixture is mixed and discharged, it is placed in a 180℃ pressure aging container for 12 hours, and a cylindrical specimen is formed using a rotary compactor. Then a core sample is drilled from the center of the specimen using a drilling coring machine and cut into standard sizes. One group includes 3 parallel specimens. The cut specimens are placed in a temperature-controlled box that has reached 20℃ for at least 5 hours, and a standard uniaxial compression dynamic modulus test is performed with a loading frequency of 10Hz.

[0076] Example 1

[0077] Rubber modified asphalt accounts for 4.5% of the mineral mass; the composite fibers used are glass fiber and carbon fiber, with a mass ratio of 1:4.

[0078] In this embodiment, two groups of tests are set up. Group A is not added with composite fibers and serves as a control group; Group B is added with composite fibers accounting for 0.1% of the total mass of the mixture.

[0079] Prepare Group A rubber modified asphalt mixture according to the following steps:

[0080] Step 1: Preheat the mixing pot to 185°C, add preheated stone into the mixing pot, and stir for 60 seconds;

[0081] Step 2: Add rubber-modified asphalt preheated to 185°C into the mixing pot and stir for 90 seconds;

[0082] Step 3: Add 50% of the mineral powder preheated to 185°C into the mixing pot and discharge the material after stirring for 60 seconds.

[0083] Prepare Group B composite fiber rubber modified asphalt mixture according to the following steps:

[0084] Step 1: Preheat the mixing pot to 185°C, add the preheated ore into the mixing pot, then add the glass fiber, and stir for 60 seconds;

[0085] Step 2: Add rubber-modified asphalt preheated to 185°C into the mixing pot and stir for 60 seconds;

[0086] Step 3: Add 50% of the mineral powder preheated to 185°C into the mixing pot and stir for 60 seconds;

[0087] Step 4, mixing the carbon fiber and the remaining 50% of the mineral powder preheated to 185° C.;

[0088] Step 5: Add the mixed carbon fiber and mineral powder into the mixing pot, stir for 90 seconds and then discharge.

[0089] Table 2 Specimen volume parameters and performance test results after aging

[0090]

[0091] It can be seen from Table 2 that, under the same volume parameters and test conditions, after the addition of 0.1% composite fiber to the total mass of the ARHM25 rubber modified asphalt mixture, after aging and freeze-thaw damage, the freeze-thaw splitting strength ratio increased from 80.3% to 88.5%, an increase of 10.2%, and the long-term interfacial bonding strength was effectively improved; the uniaxial compression dynamic modulus increased from 4650MPa to 7230MPa, an increase of 2580MPa, an increase of 55.5%, and the ability to resist compression deformation was significantly improved.

[0092] Example 2

[0093] The mass ratio of rubber modified asphalt to mineral material is 4.8%; the composite fibers used are glass fiber and carbon fiber, with a mixing amount of 0.2%.

[0094] In this embodiment, there are 5 groups of tests AE, the mass ratio of glass fiber to carbon fiber in group A is 1:2, the mass ratio of glass fiber to carbon fiber in group B is 1:3, the mass ratio of glass fiber to carbon fiber in group C is 1:4, the mass ratio of glass fiber to carbon fiber in group D is 1:5; and the mass ratio of glass fiber to carbon fiber in group E is 1:6.

[0095] The AE group composite fiber rubber modified asphalt mixture was prepared according to the following steps:

[0096] Step 1: Preheat the mixing pot to 195°C, add the preheated ore into the mixing pot, then add the glass fiber, and stir for 60 seconds;

[0097] Step 2: Add rubber-modified asphalt preheated to 190°C into the mixing pot and stir for 60 seconds;

[0098] Step 3: Add 50% of the mineral powder preheated to 195°C into the mixing pot and stir for 60 seconds;

[0099] Step 4, mixing the carbon fiber and the remaining 50% of the mineral powder preheated to 195° C.;

[0100] Step 5: Add the mixed carbon fiber and mineral powder into the mixing pot, stir for 90 seconds and then discharge.

[0101] Table 3 Specimen volume parameters and performance test results after aging

[0102]

[0103] As can be seen from Table 3, with the increase of the mass ratio of glass fiber to carbon fiber, the increase in the void ratio of ARHM25 rubber modified asphalt mixture gradually decreases; the freeze-thaw splitting strength ratio increases first and then decreases, and it decreases significantly when the mass ratio is 1:6; the uniaxial compression dynamic modulus gradually increases, but the increase is not obvious when the mass ratio is 1:6. In summary, it can be proved that the reasonable mass ratio of glass fiber to carbon fiber in the composite fiber is 1:3 to 1:5.

[0104] Example 3

[0105] The mass ratio of rubber modified asphalt to mineral material is 5.0%; the composite fibers used are glass fiber and carbon fiber, and the mass ratio is 1:4.

[0106] In this embodiment, there are three groups of tests, AC, in which group A is added with 0.1% of the total mass of the mixture of composite fibers, group B is added with 0.2% of the total mass of the mixture of composite fibers, and group C is added with 0.3% of the total mass of the mixture of composite fibers.

[0107] The AC group composite fiber rubber modified asphalt mixture was prepared according to the following steps:

[0108] Step 1: Preheat the mixing pot to 190°C, add the preheated ore into the mixing pot, then add the glass fiber, and stir for 60 seconds;

[0109] Step 2: Add rubber-modified asphalt preheated to 190°C into the mixing pot and stir for 60 seconds;

[0110] Step 3: Add 50% of the mineral powder preheated to 190°C into the mixing pot and stir for 60 seconds;

[0111] Step 4, mixing the carbon fiber and the remaining 50% of the mineral powder preheated to 190° C.;

[0112] Step 5: Add the mixed carbon fiber and mineral powder into the mixing pot, stir for 90 seconds and then discharge.

[0113] Table 4 Specimen volume parameters and performance test results after aging

[0114]

[0115] As can be seen from Table 4, with the increase of the proportion of composite fiber, the void ratio of ARHM25 rubber modified asphalt mixture increases slightly. For every 0.1% increase in fiber dosage, the void ratio increases by about 0.1%; the freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus both increase gradually, but the increase is not obvious when the dosage is 0.3%; and during the mixing process, agglomeration begins to occur, and the mixing time needs to be increased. In terms of economy and operability, there is no advantage. Therefore, it can be proved that the reasonable dosage range of composite fiber is 0.1% to 0.2%.

[0116] Example 4

[0117] The mass ratio of rubber modified asphalt to mineral material is 5.0%; the composite fibers used are glass fiber and carbon fiber, and the mass ratio is 1:4.

[0118] In this embodiment, there are 4 groups of tests AD, in which group A adds 0.1% of the total mass of the mixture with composite fiber, group B adds 0.1% of the total mass of the mixture with glass fiber, group C adds 0.1% of the total mass of the mixture with carbon fiber, and group D does not add any fiber.

[0119] Prepare Group A rubber modified asphalt mixture according to the following steps:

[0120] Step 1: Preheat the mixing pot to 185°C, add preheated stone into the mixing pot, then add glass fiber, and stir for 60 seconds;

[0121] Step 2: Add rubber-modified asphalt preheated to 185°C into the mixing pot and stir for 60 seconds;

[0122] Step 3: Add 50% of the mineral powder preheated to 185°C into the mixing pot and stir for 60 seconds;

[0123] Step 4, mixing the carbon fiber and the remaining 50% of the mineral powder preheated to 185° C.;

[0124] Step 5: Add the mixed carbon fiber and mineral powder into the mixing pot, stir for 90 seconds and then discharge.

[0125] Prepare Group B and Group C rubber modified asphalt mixtures according to the following steps:

[0126] Step 1: Preheat the mixing pot to 185°C, add preheated stone into the mixing pot, then add glass fiber or carbon fiber, and stir for 60 seconds;

[0127] Step 2: Add rubber-modified asphalt preheated to 185°C into the mixing pot and stir for 120 seconds;

[0128] Step 3: Add mineral powder preheated to 185°C into the mixing pot and discharge after stirring for 90 seconds.

[0129] Prepare Group D rubber modified asphalt mixture according to the following steps:

[0130] Step 1: Preheat the mixing pot to 185°C, add the preheated ore into the mixing pot, and stir for 60 seconds;

[0131] Step 2: Add rubber-modified asphalt preheated to 185°C into the mixing pot and stir for 90 seconds;

[0132] Step 3: Add mineral powder preheated to 185°C into the mixing pot and discharge the material after stirring for 60 seconds.

[0133] Table 5 Specimen volume parameters and performance test results after aging

[0134]

[0135] It can be seen from Table 5 that compared with the control group D, after adding 0.1% glass fiber by mass of the mixture, the freeze-thaw splitting strength ratio of the rubber modified asphalt mixture increased from 81.4% to 83.5%, an increase of 2.1%, an increase of 2.6%; the uniaxial compression dynamic modulus increased from 4070MPa to 5047MPa, an increase of 977MPa, an increase of 24%.

[0136] After adding 0.1% carbon fiber to the mixture, the freeze-thaw splitting strength ratio of the mixture increased from 81.4% to 83.1%, an increase of 1.7%, an increase of 2.1%; the uniaxial compression dynamic modulus increased from 4070MPa to 5615MPa, an increase of 1545MPa, an increase of 38%.

[0137] After adding 0.1% composite fiber to the mixture, the freeze-thaw splitting strength ratio of the mixture increased from 81.4% to 87.5%, an increase of 6.1%, an increase of 7.5%; the uniaxial compression dynamic modulus increased from 4070MPa to 6935MPa, an increase of 2865MPa, an increase of 70.4%.

[0138] It can be seen that after adding glass fiber and carbon fiber respectively, the freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus of rubber modified asphalt mixture are improved, especially the increase of uniaxial compression dynamic modulus is obvious. After adding mixed fiber, the increase of freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus of rubber modified asphalt mixture is greater than the increase of freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus of rubber modified asphalt mixture with glass fiber and carbon fiber respectively, and greater than the sum of the increase of adding glass fiber alone and adding carbon fiber alone.

[0139] Comparative Example 1

[0140] This comparative example is similar to the experiment of group A of Example 4, except that the mineral powder is not added in batches but added all at once in step 3. The experimental results are shown in Table 6.

[0141] Comparative Example 2

[0142] This comparative example is similar to the experiment of group A of Example 4, except that the order of adding glass fiber and carbon fiber is reversed. The experimental results are shown in Table 6.

[0143] Comparative Example 3

[0144] This comparative example is similar to the experiment of group A of embodiment 4, except that the length of the carbon fiber is 7±1 mm, while the length of the glass fiber is 5±1 mm, and the lengths of the two are inconsistent. The experimental results are shown in Table 6.

[0145] Comparative Example 4

[0146] This comparative example is similar to the experiment of group A of Example 4, except that the length of the carbon fiber and the glass fiber is less than 4 mm, which is not within the critical sieve hole size of the stone (4.75-9.5 mm). The experimental results are shown in Table 6.

[0147] Table 6 Specimen volume parameters and performance test results after aging

[0148]

[0149] It can be seen from Table 6 that the one-time addition of mineral powder, the reversal of the order of adding glass fiber and carbon fiber, the inconsistent lengths of carbon fiber and glass fiber, and the lengths of carbon fiber and glass fiber not being between the key sieve hole particle size of stone (4.75-9.5mm) will all affect the freeze-thaw splitting strength ratio and uniaxial compression dynamic modulus of rubber modified asphalt mixture, thereby leading to insufficient interfacial bonding strength and compression deformation resistance of ultra-high rubber modified asphalt mixture after aging.

[0150] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a composite fiber rubber modified asphalt mixture, characterized in that: The following steps are involved: Step 1: Add preheated stone to the preheated mixing pot, then add glass fiber and stir; Step 2: Add rubber modified asphalt into the mixing pot and stir; Step 3: Add some mineral powder to the mixing pot and stir; Step 4: Mix the carbon fiber and the remaining mineral powder; Step 5: Add the mixed carbon fiber and mineral powder into a mixing pot, stir, and discharge to obtain a composite fiber rubber modified asphalt mixture.

2. The preparation method according to claim 1, characterized in that: In step 1, the preheating temperature of the mixing pot is 185-195°C.

3. The preparation method according to claim 1 or 2, characterized in that: In step 1, the stirring time is 60s.

4. The preparation method according to claim 3, characterized in that: The mineral powder in step 3 and step 4 each accounts for 50%.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the glass fiber to the carbon fiber is 1:3 to 1:

5.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the stone material to the mineral material is 96:

4.

7. The preparation method according to claim 5 or 6, characterized in that: The grading type of the stone is ARHM-25 type grading.

8. The preparation method according to claim 1, characterized in that: The rubber modified asphalt is an ultra-high-content rubber modified asphalt with a rubber powder mass fraction of more than 70 parts.

9. The preparation method according to claim 1, characterized in that: In step 5, the stirring time is 90s.

10. A composite fiber rubber modified asphalt mixture, characterized in that: The preparation method is described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Carbon fiber rubber modified asphalt mixture and preparation method thereof

    CN112374805A

  • Glass fiber rubber modified asphalt mixture and preparation method thereof

    CN112374806A